EKSPLORASI PRAGMATISME DALAM ARTIKEL ILMIAH POPULER MAHASISWA - Kustina, Rika; Syihabuddin, Syihabuddin; Talitha, Stella; Nissa, Barkatun; Bujaya, Muhammad; Arianto, Arianto; Trisnawati, Trisnawati; Nina, Nina (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2025)
This study aims to explore language practices in popular scientific articles written by students using a pragmatic hermeneutic approach based on the ideas of Charles S. Peirce, William James, and John Dewey. This study focuses on how language in these writings not only functions as a means of conveying information but also as a social action that shapes consciousness, conveys values, and influences readers. The method used is descriptive qualitative with philosophical discourse analysis techniques applied to five student articles published in popular online media. The results of the study indicate that the language in these articles is reflective, persuasive, and transformative. Students position themselves as social subjects addressing historical, moral, cultural, and economic issues through language that shapes action. Popular scientific articles prove to be a medium for the practice of pragmatic language philosophy, where meaning is formed within a social context and directed toward real change.